2021
DOI: 10.3390/pr9010117
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Antimony Removal by Coagulation-Flocculation-Sedimentation Process Using Response Surface Methodology

Abstract: Coprecipitation-adsorption plays a significant role during coagulation-flocculation-sedimentation (C/F/S) of antimony (Sb) in water. This work uses a Box–Behnken statistical experiment design (BBD) and response surface methodology (RSM) to investigate the effects of major operating variables such as initial Sb(III, V) concentration (100–1000 µg/L), ferric chloride (FC) dose (5–50 mg/L), and pH (4–10) on redox Sb species. Experimental data of Sb(III, V) removal were used to determine response function coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…A recent study [ 7 ] attempts to explain the influence of pH and HA on pentavalent [Sb(V)] and trivalent [Sb(III)] removal with particular emphasis on the physicochemical properties of Fe precipitates. The significant effect of pH on Sb(V) removal has been evidenced, particularly at alkaline conditions [ 6 , 9 , 16 ]. The presence of hydrophobic organic compounds such as HA may alter the surface properties of Fe flocs, thereby affecting the overall performance of the coagulation process [ 7 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study [ 7 ] attempts to explain the influence of pH and HA on pentavalent [Sb(V)] and trivalent [Sb(III)] removal with particular emphasis on the physicochemical properties of Fe precipitates. The significant effect of pH on Sb(V) removal has been evidenced, particularly at alkaline conditions [ 6 , 9 , 16 ]. The presence of hydrophobic organic compounds such as HA may alter the surface properties of Fe flocs, thereby affecting the overall performance of the coagulation process [ 7 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the cubic model showed aliasing owing to lack of data points availability for model coefficients estimation. Therefore, further analysis was performed using the quadratic model [33].…”
Section: Identifying Best Response Function Using Statistical Analysismentioning
confidence: 99%
“…An earlier study [32] also showed applicability of RSM for simultaneous removal of arsenic (As) and DOC during the chemical coagulation process. Our previous study [33] investigated Sb removal by varying initial Sb concentration, FC dosage, and pH values using RSM and the Box-Behnken design (BBD) model. However, the developed model did not account for the interaction of organic species, and up to 12% of total variation in Sb removal response was not described by the model.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the possible health risks associated with arsenic exposure, the World Health Organization (WHO) has recommended a more stringent limit of 10 μg L −1 as the maximum permissible arsenic level in drinking water. 2 Many strategies like oxidation, 3 ion exchange, 4 reverse osmosis, adsorption, 5,6 extraction 7,8 and biosorption 9 have been employed for remediating arsenic polluted water. Among such techniques, adsorption is considered as a practical approach owing to its simple operation, cost-effective nature and efficient capture of metal ions even at low concentrations.…”
Section: Introductionmentioning
confidence: 99%